1977
DOI: 10.1128/jb.130.1.1-3.1977
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of lipopolysaccharides from cell walls of blue-green algae of the genus Phormidium

Abstract: Lipopolysaccharide (LPS) fractions were isolated from three species of bluegreen algae of the genus Phormidium, namely, P. africanum, P. laminosum, and P. uncinatum, by using a phenol-water procedure followed by exhaustive extraction with ammonium oxalate. The materials obtained were shown to be closely related biochemically. Nearly 60% of the LPS consisted of the polysaccharides galactose, glucose, mannose, xylose, arabinose, and rhamnose and an unidentified, fast-moving sugar residue. In addition, glucosamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…shown to be nontoxic when injected into mice (15)(16)(17)(18)(19). Extracts from fi lamentous cyanobateria other than Oscillatoria Planktothrix FP1 (Oscillatoria Neglecta, environmentally isolated Oscillatoria Sp.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…shown to be nontoxic when injected into mice (15)(16)(17)(18)(19). Extracts from fi lamentous cyanobateria other than Oscillatoria Planktothrix FP1 (Oscillatoria Neglecta, environmentally isolated Oscillatoria Sp.…”
Section: Articlementioning
confidence: 99%
“…LPS derived from cyanobacteria and from Gram-negative bacteria diff ers in both chemical and biological characteristics. In general, LPS from cyanobacteria lacks l-glycero-d-mannoheptose and phosphate groups, has long-chain saturated and unsaturated fatty acids, and very low content of 2-keto-3-deoxyoctonate (15)(16)(17)(18)(19). Furthermore, cyanobacterial LPS shows minimal or no toxicity in mice, whereas no data are available concerning its activity on human cells (16,17).…”
mentioning
confidence: 99%
“…For example, recent studies have indicated that cyanobacterial LPS lacks strong endotoxic activity because of lipid A structures that differ from those generally conserved among proteobacteria (Rapala et al 2002;Stewart et al 2006). In addition, almost all cyanobacterial LPSs are devoid of 3-deoxy-D-manno-oct-2-ulosonic acid (KDO), heptose and phosphate components (Weckesse et al 1974;Mikheyskaya et al 1977;Schmidt et al 1980a;Hoiczyk and Hansel 2000), which are commonly observed in the R-core region of proteobacterial LPS. Instead, other saccharide units such as glucose are the main components of some cyanobacterial LPS (Snyder et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative derivatives for carbohydrate analysis have included aldonitrile acetates (Mikheyskaya et al 1977), o-alkylalditol acetates (Yamaguchi & Okamoto 1977), alditol acetates (Cooper et al 1975) and methyl alditol acetates (Freedman et al 1978).…”
mentioning
confidence: 99%